How I learned to fly - Stine, R. L. (New York : Scholastic, 1997)
Jack Johnson finds a book that tells how humans can learn to fly and hopes to use his knowledge to show-up his classmate Wilson Schlame; but when the news gets out that Jack can fly, things start to get out of hand and he questions whether flying is really the way to go.
3.8
5-8
Keywords: Competition (Psychology) -- Juvenile fiction; Flight -- Juvenile fiction; Competition (Psychology) -- Fiction; Flight -- Fiction; Horror stories; Competition -- Fiction; Flight -- Fiction; Horror fiction; Horror fiction